Plan de negocio para sistema de autolimpieza y eficiencia de paneles fotovoltaicos (2017)
The present paper aims to propose alternative Solutions to the problems that arise in the implementation of solar energy, as clean and safe energy. These disadvantages have generated that this alternative has not been used in Colombia in a massive way. These problems are pollution, position with respect to the sun and temperature, so three mechanisms are present to keep the solar panels clean and in good condition making them much more useful and therefore more profitable as generators of energy: The first mechanism is cleaning, which is made up of a tube with holes, a servomotor and a compressor. The purpose of this mechanism is to blow the photovoltaic panel so that it does not have impurities on its surface. Air is used to not count on water costs for cleaning. This mechanism sweeps over the panel at night time so it will not block the light of day. The second mechanism is a structure that allows the rotation of the panel during the day, programmed by means of a digital dock to calculate the angle that best allows him to obtain the best solar radiation. For the movement of this mechanism a stepper motor is used. The third mechanism is refrigeration, improving its efficiency after its temperature exceeds 25 degrees Celsius. This mechanism has a pipe that will circulate water, a water pump and temperature sensors. The pipe will go to the back of the panel, using the Fourier Law, which States that "conduction of heat or transmission of heat by conduction is a process of heat transmission based on direct contact between bodies, without exchange of matter, for The one that the heat flows from a body of higher temperature to one of lower temperature that is in contact with the first", in this way will reduce the temperature of the panel. Taking into account the above, a business plan was devised that would allow to move in the market, these three mechanisms to improve the efficiency of solar panels. From the market study it was concluded that the investment by the final customer is high and does not recover quickly, therefore, it was considered that the target audience are the companies that are dedicated to the sale of solar equipment that have this Database of people interested in the product and who as distributors could have greater efficiency in the management of the market. For the ideation of these mechanisms, mechanical engineers participated in the design and calculation of each device, electronic engineers for the design and calculation of the loads necessary for the handling of engines and pumps to be used. The interdisciplinary work led to the solution with simple and easy to use and at the same time economic mechanisms. The tools used were all those based on quality standards, which provide engineering design, based on physics and principles of mechanics; Additional the use of CNC machinery, guarantees the precision in the manufacture of each one of the parts.